Simultaneous Optimization of Process Design and Solvent in a Flowsheet Simulator. Issue 3 (18th November 2022) - Stavrou, Marina; Hoeller, Johannes; Seidel, Tobias; Mairhofer, Jonas; Asprion, Norbert
Abstract: For processes using auxiliaries, the selection of the process fluid should not be separated from the process design. To solve the simultaneous process and fluid optimization problem for industrial applications, a flowsheet simulator is required. The implementation of the two‐stage CoMT‐CAMD approach in CHEMASIM, the in‐house flowsheet simulator of BASF SE, allows for large process topologies with a large variety of unit operation models to be modeled, while sustainability criteria like cost and life cycle assessment (LCA) objectives, are directly accessible and can be solved with single or multicriteria optimization methods. The modifications required for the implementation and the user interface designed for this purpose are presented here. Abstract : To solve the simultaneous process and fluid optimization problem for industrial applications, the two‐stage CoMT‐CAMD approach is implemented in CHEMASIM, the in‐house flowsheet simulator of BASF SE. The required modifications of the method and the extension of the user interface of CHEMASIM results are presented for single and multiobjective optimization problems of process‐fluid selection and design.